DNA barcoding, phylogenetic relationships and speciation of Genus: Plectropomus in Andaman coast - PM, Mohan; V, Sachithanandam; P, Dhivya; N, Muruganandam; R, Baskaran; IK, Chaaithanya; P, Vijayachari (Journal of Research in Biology, 2011)
DNA barcode technique has been recently promoted as a method for both assigning specimens to known species and for discovering new and cryptic species. The present study carried out for the barcode sequences for identification of the Plectropomus leopardus. The results of shorter sequence 113bp of Plectropomus leopardus is effective to identify a specimen and confirm up to a species level. This sequence also exhibited deep interspecific divergences that allowed for efficient discrimination among the Grouper species. This mini barcode sequence technique might be used efficiently to distinguish Plectropomus leopardus with minimal expenditure and efforts. These results also support that formalin fixation samples can also be used for DNA molecular taxonomy